PENGARUH PEMBIAYAAN, SIMPANAN MUDHARABAH, DAN BIAYA OPERASIONAL BANK TERHADAP SYARIAH MUQASHID INDEX PADA BANK UMUM SYARIAH DI INDONESIA - Ririn Sari Dewi (Universitas Pamulang, 2018)
AbstractThe purpose of this research is to analyse the influence of the Financing, Mudharabah Saving Account, and the Bank Operational Cost to the Syariah Muqasid Index of the Bank Umum Syariah (BUS) in Indonesia, The researcher use 55 sample of 11 Bank Umum Syariah (BUS) in Indonesia within 5 years of annual report period. In this research, the researcher use the Multiple Regression af statistical method to analyse the data. The result of this research shows that the Financing, Mudharabah Saving Account, and the Bank Operational Cost has positive influence simultaneously to the Syariah Muqasid Index, and the Financing has positive influence simultaneously to the Syariah Muqasid Index, and the Mudharabah Saving Account has positive influence simultaneously to the Syariah Muqasid Index. And researcher has found that the Mudharabah Saving Account variable has no influence directly to the performance of the Syariah Muqasid Index, because the Mudharabah Saving Account variable is distributed by the bank to the Financing Variable depends on the needs of the bank customers dan the result is divided by the profit sharing according the understanding which is made in the first MOU. KeyWords :the Financing, Mudharabah Saving Account, and the Bank Operational Cost to the Syariah Muqasid Index of the Bank Umum Syariah (BUS) in Indonesia